Odpowiedzi

2010-01-21T15:44:37+01:00
C)
{x+y/2+2x+y/3=4 /*6
{2x-y/4-x+y/6=-¹/₆ /*12 ułamki sie skracają
[3x+3y+4x+2y=24
[6x-3y-2x-2y=-2
{7x+5y=24
{4x-5y=-2
~~~~~~~~~~~~
11x=22/:11
__x=2
7x+5y=24
7*2+5y=24
14+5y=24
5y=24-14
5y=10/:5
y=2 rozwiązanie to {x=2 {y=2
d)
{2x-y/3+x+2y/6=-2½
{2x+y/4-2x-y/2=1½
[2x-y/3+x+2y/6=-⁵/₂ /*6
[2x+y/4-2x-y/2=³/₂ /*4
{4x-2y+x+2y=-15
{2x+y-4x+2y=6
[5x=-15/:5
[-2x+3y=6
{x=-3
{-2*(-3)+3y=6
[x=-3
[6+3y=6
{x=-3___________________{x=-3
{3y=0/:3________________{y=0
a) zad 9
{(x-5)²+x(3-x)+5y=-1
{(y-3)²+(5-y)(5+y)+x=6
[x²-10x+25+3x-x²+5y=-1
[y²-6y+9+25+5y-5y-y²+x=6
{-7x+5y=-26
{x-6y=-28/*7
[-7x+5y=-26
[7x-42y=-196
```````````````
____-37y=-222/(-37)
_______y=6
-7x+5y=-26
-7x+5*6=-26
-7x+30=-26
-7x=-56/:(-7)
___x=8 __________________{x=8___{y=6
b)
{(x+2)²-(x-3)(x+3)-2y=-1
{(y-8)²-(y-10)²+3x=14
[x²+4x+4-(x²+3x-3x-9)-2y=-1
[y²-16y+64-(y²-20y+100)+3x=14
{x²+4x+4-x²-3x+3x+9-2y=-1
{y²-16y+64-y²+20y-100+3x=14
[4x-2y=-14/*2
[3x+4y=50
{8x-4y=-28
{3x+4y=50
~~~~~~~~~~~~
11x=22/:11
___x=2
8x-4y=-28
8*2-4y=-28
16-4y=-28
-4y=-28-16
-4y=-44/:(-4)
___y=11
c)
{(4-x)²-x(x-3)+4y=-7
{(y+1)²+y(5-y)-3x=1
[16-8x+x²-x²+3x+4y=-7
[y²+2y+1+5y-y²-3x=1
{-5x+4y=-23/*3
{-3x+7y=0/*(-5)
[-15x+12y=-69
[15x-35y=0
````````````
_____-23y=-69/:(-23)
________y=3
-5x+4y=-23
-5x+4*3=-23
-5x+12=-23
-5x=-35/:(-5)
__x=7
d)
{(x-8)²-(x-9)²=2y-7
{(y+1)²-(y-3)(y+3)=3x-6
[x²-16x+64-(x²-18x+81)=2y-7
[y²+2y+1-(y²+3y-3y-9)=3x-6
{x²-16x+64-x²+18x-81=2y-7
{y²+2y+1-y²-3y+3y+9=3x-6
[2x-2y=10
[-3x+2y=-7
``````````
___-x=3/*(-1)______x=3
2x-2y=10
2*3-2y=10
6-2y=10
-2y=4/:(-2)
__y=-2
Najlepsza Odpowiedź!
2010-01-21T17:20:05+01:00
C)
(4-x)2 - x(x-3) + 4y = - 7
(y+1)2 + y(5-y) - 3x = 1
16 - 8x + x2 - x2 + 3x + 4y = -7
y2 + 2y + 1 + 5y - y2 - 3x = 1
-5x + 4y = -23
-3x + 7y = 0 /: 3
-5x + 4y = -23
-x = - 7/3 y /: (-1)
-5x + 4y = -23
x= 7/3y
-5(7/3y) + 4y = -23
x= 7/3y
-35/3y + 4y = -23
x= 7/3y
-39/3y = -23 /:(-1)
x= 7/3y
39/3y =23
x= 7/3y
y= 13/23
x = 91/69




d)
(x-8)2 - (x-9)2 = 2y - 7
(y+1)2 - (y -3 )(y+3) = 3x - 6
x2 - 16x + 64 - ( x2 - 18x + 81) = 2y - 7
y2 + 2y + 1 - ( y2 + 3y - 3y - 9) = 3x - 6
x2 - 16x + 64 - x2 + 18x - 81 = 2y - 7
y2 + 2y + 1 - y2 - 3y + 3y + 9 = 3x - 6
2x - 2y = 10 / : 2
-3x + 2y = -16
x - y = 5
-3x + 2y = -16
x= 5 + y
-3(5 + y) + 2y = -16
x= 5 + y
-15 - 3y + 2y = -16
x= 5 + y
-1y = -1
x= 5 + y
y = 1
x = 6



1 5 1